1998
DOI: 10.3109/01902149809087384
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gap Junctions in Lung Neoplasia

Abstract: Reduced gap junctional intercellular communication (GJIC) has been noted in many types of neoplastic cells and may contribute to the neoplastic phenotype. This study assessed GJIC (by fluorescent dye-coupling) and gap junction protein (connexin) expression in mouse and human lung carcinoma cell lines and investigated whether reduced GJIC was involved in their neoplastic phenotype. Dye-coupling and connexin43 (Cx43) expression were much lower in most of the carcinoma lines (16 of 22) compared to nontransformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 38 publications
(16 reference statements)
0
26
1
Order By: Relevance
“…Although previous studies have established that connexins are expressed in the pulmonary system, the precise influence of connexins on development and physiology has yet to be determined (13)(14)(15)(16). Although several studies have suggested the influence of connexins on lung tumor cell behavior (12,17,18), no conclusive studies have linked connexin deficiency with pulmonary oncogenesis in situ. Here, we evaluated the role of Cx32 in mouse lung carcinogenesis with a genetically deficient mouse model in combination with the chemical lung carcinogen diethylnitrosamine and observed increased tumorigenesis strongly implicating Cx32 as a tumor suppressor in mouse lung.…”
Section: Introductionmentioning
confidence: 93%
“…Although previous studies have established that connexins are expressed in the pulmonary system, the precise influence of connexins on development and physiology has yet to be determined (13)(14)(15)(16). Although several studies have suggested the influence of connexins on lung tumor cell behavior (12,17,18), no conclusive studies have linked connexin deficiency with pulmonary oncogenesis in situ. Here, we evaluated the role of Cx32 in mouse lung carcinogenesis with a genetically deficient mouse model in combination with the chemical lung carcinogen diethylnitrosamine and observed increased tumorigenesis strongly implicating Cx32 as a tumor suppressor in mouse lung.…”
Section: Introductionmentioning
confidence: 93%
“…Decreased GJIC may result in isolated cells receiving fewer inhibitory signals, allowing for the accumulation of positive signals that lead to uncontrolled cell division and dedifferentiation (Ruch, 1994). For example, malignant transformation of lung (Ruch et al, 1998) and liver (Trosko and Ruch, 1999) cells has been linked to a loss of GJIC. Several carcinogens and oncogene products have been shown to decrease connexin expression (Lau et al, 1992;Yamasaki et al, 1999), while differentiating and antineoplastic agents (e.g., retinoids and vitamin D) upregulate GJIC (Schmidt et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…21 Compared to normal lung epithelial cells, Cx43 expression is significantly lower in lung cancer cell lines. 33,34 The Cx43-mediated GJIC pathway is implicated in the observed bystander effect in cancer gene therapy. 35 In parallel studies, iodide significantly induces the expression of Cx43, suggesting that Cx43 plays a critical role in iodide-induced GJIC activity in NIS/TPO-genetically modified NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%